Effects of training cessation on muscle strength, body composition and resting hormones in elite kayakers - Sanchez-Medina, L.; Carrasco, L.; Garcia-Pallares, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In top-level athletes, there is a need to incorporate some regeneration period after the conclusion of the main event of the season in order to allow for physical and mental relief before the start of a new training cycle (Bompa, 1999). Usually, this layoff is associated with performance declines that are dependent on the chosen recovery strategy (reduced training or inactivity), initial fitness level, and total time under reduced or absence of training stimuli (Mujika and Padilla, 2000). However, the consequences of these post-season breaks on performance are not fully understood. The aim of this study was to analyze changes in muscle strength, body composition and resting hormones during 5-wk of training cessation (TC) in ten elite kayakers. Methods: Maximal strength and power testing, body composition assessment and blood sampling were conducted 7-d before the start of the Flatwater Racing World Championships (T1), and after 5-wk of TC (T2). One-repetition maximum (1RM) and mean velocity with 45% 1RM load (V45%) were assessed in the bench press (BP) and prone bench pull (PBP) exercises. Body fat (BF) and muscle mass (MM) were estimated from anthropometric measurements. Blood samples were assayed for testosterone (T) and cortisol (C) by radioimmunoassay. Results: From T1 to T2, significant declines in 1RM values were found for BP (-9%) and PBP (-8%). Similarly, V45% significantly decreased by 13% and 9% for BP and PBP, respectively. No significant changes were observed in body mass. However, BF significantly increased (21%) and MM decreased (6%) from T1 to T2. Cortisol decreased (-30%) and T increased (12%); consequently, T/C drastically increased (70%). Discussion: The main findings of the present study were that 5-wk of TC resulted in significant reductions in maximal strength and muscle power, decreases in muscle mass and increments in body fat, elevation in T and T/C and reduction in C. Thus, short-term TC resulted in a true detraining effect, with large declines experienced in physiological markers of highly conditioned athletes. Positive changes were those related to an apparently increased androgenic-anabolic activity, possibly due to the body`s reaction to combat the catabolic processes induced by the high levels of physical and mental stress experienced during the precedent season. Our findings support previous research (Häkkinen et al., 1981; Izquierdo et al., 2007), and demonstrate the need of a maintenance program of reduced training to avoid excessive declines in neuromuscular function in cases where a prolonged break from formal training is required.